PROHIBITION OF MARRIAGE BETWEEN TWO SIBLINGS AT THE SAME TIME (An Examination of Islamic Law and the Cultural Reality of the Pasir Sialang Village Community in Kampar Regency, Riau) - Muh Rizki; Andre Afrilian; Amrin Borotan; Ardiansyah (Syaksia: Jurnal Hukum Perdata Islam, 2025)
In the current discourse on Islamic family law, cultural aspects cannot be separated from the scope of family law, especially marriage. As in the view of the Pasir Sialang Village community, when conducting a marriage, considerations must be taken into account, such as the community's perception of the prohibition of two siblings marrying at the same time. The purpose of this article is to determine the views of the Pasir Sialang Village community regarding the prohibition of marriage between two siblings at the same time and the impact of this prohibition from a cultural anthropology perspective. This research is empirical legal research using a cultural anthropology approach. The results of this study confirm the existence of a prohibition on the marriage of two siblings at the same time and the community's belief in the impact of such marriages. This is due to the influence of traditional culture and the reality of beliefs that exist in the community as a result of violating established rules, as evidenced by past occurrences in the Pasir Sialang community. Such as divorce, death, and miscarriages during pregnancy. From a cultural anthropology perspective, the phenomenon of marriage prohibition cannot be permanently prohibited, due to social considerations that influence understanding in society.